Health behaviors in sexual experiences of women in prison - Oliveira,Karlayne Reynaux Vieira de (2019)
ABSTRACT Objective: to describe the health behaviors related to the sexual experiences of women in the female prison system from January to March, 2017. Method: descriptive study with a qualitative approach. A semi-structured questionnaire containing mixed questions and patient records was used. The data analysis was performed through the Bardin’s content analysis and adopted as reference the Theory of Basic Human Needs. Results: 18 women, young, single, brown, with a complete fundamental level participated in the study. After this characterization, two categories were evidenced: Health behaviors in sexual experiences and Health care in the face of sexual experiences. 33.3% reported on health behaviors such as Sexually Transmitted Infections (STIs), 27.7% associated with male condom use, 16.6% on prevention of unwanted pregnancies, 11.1% on health care and hygiene. Final considerations: it was evidenced that the health behaviors reported by women in sexual experiences are associated with actions to prevent STIs, use of condoms, unwanted pregnancies, and health and hygiene care. However, it is possible to infer that they understand and possess superficial knowledge about health behaviors and that there is no adoption of regular practice in their sexual experiences.